An ultra-compact planar bandpass filter with open-ground spiral for wireless application - Ma, Kaixue (2010)
A common via filter is investigated and designed by using a proposed scalable lumped circuit model. The model-based result of the filter agrees well with that of the measurement. An ultra-compact open-ground spiral filter is proposed based on the common via filter. The open-ground spiral resonators are used to design second-order and fourth-order bandpass filters. The filter layouts, which affect filter performance in both passband and stopband, are investigated. The advantages of the open-ground spiral filter include not only its ultra-compact size but also its additional transmission zero points and controllable stopband.